Effectiveness of PowerPoint Media in Improving Letter Recognition Skills among Indonesian Preschoolers - Rina Miranda; Leopoldina Da Silva (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Purpose – This study investigates whether PowerPoint-based media can improve early literacy skills, focusing on letter recognition among preschool children. Traditional methods often fail to engage young learners effectively, and this research aims to explore the potential of multimedia tools to enhance literacy outcomes.Design/methods/approach – A quantitative, pre-experimental one-group pre-test-post-test design was used, involving 18 children aged 5–6 years from TK Tunas Mandiri Sungai Raya, Indonesia. Data were collected through structured observation using a checklist assessing letter identification, sound pronunciation, and letter-image association. Statistical analysis was conducted via paired sample t-tests in SPSS.Findings – Results showed a significant increase in letter recognition scores, from a mean of 4.67 in the pre-test to 8.61 in the post-test. These findings suggest that PowerPoint can be a practical and effective tool to support early literacy learning, engaging children through visual and auditory stimuli.Research implications/limitations – The study’s limitations include the absence of a control group and a small sample size, which limit generalizability. Nonetheless, this research contributes valuable insights into how simple digital tools can enhance literacy education in early childhood settings, particularly where resources are limited